Reforms to the laws on the surveillance of private communications - Kruyer, Catherine (Department of Public Law, 2025)
The right to privacy is central to our constitutional order, which is founded on human dignity. The ability of the State to invade the privacy of our communications threatens the personal space within which we live “our daily lives”. The Constitutional Court in AmaBhungane evaluated the law regulating communications surveillance – the Regulation of Interception of Communications and Provision of Communications-Related Information Act 70 of 2022 (“RICA”) – and declared RICA inconsistent with the Constitution in five respects. The judgment and order of the Constitutional Court necessitates extensive and wide-ranging amendments to RICA to cure the defects identified by the Court. The Constitutional Court suspended the declarations of invalidity to give Parliament an opportunity to cure the defects. Moreover, the key principles recognised in the judgment of the Constitutional Court necessitate a more comprehensive review of RICA, which centres the right to privacy. The Constitutional Court recognised that State surveillance of our personal communications is an invasive violation of the right to privacy. It emphasized the importance of RICA containing adequate safeguards to ensure that there are not unnecessary invasions of the right to privacy. In this thesis, I consider the reforms required to cure the defects in RICA identified by the Constitutional Court in Amabhungane, as well as further reforms to existing laws required to ensure a human-rights centric approach to communications surveillance in South Africa.